Acid ceramidase is associated with an improved prognosis in both DCIS and invasive breast cancer. Issue 1 (31st July 2014) - Sänger, Nicole; Ruckhäberle, Eugen; Györffy, Balazs; Engels, Knut; Heinrich, Tomas; Fehm, Tanja; Graf, Anna; Holtrich, Uwe; Becker, Sven; Karn, Thomas
Abstract : Acid ceramidase (ASAH1) a key enzyme of sphingolipid metabolism converting pro‐apoptotic ceramide to sphingosine has been shown to be overexpressed in various cancers. We previously demonstrated higher expression of ASAH1 in ER positive compared to ER negative breast cancer. In the current study we performed subtype specific analyses of ASAH1 gene expression in invasive and non invasive breast cancer. We show that expression of ASAH1 is mainly associated with luminal A – like cancers which are known to have the best prognosis of all breast cancer subtypes. Moreover tumors with high ASAH1 expression among the other subtypes are also characterized by an improved prognosis. The good prognosis of tumors with high ASAH1 is independent of the type of adjuvant treatment in breast cancer and is also detected in non small cell lung cancer patients. Moreover, even in pre‐invasive DCIS of the breast ASAH1 is associated with a luminal phenotype and a reduced frequency of recurrences. Thus, high ASAH1 expression is generally associated with an improved prognosis in invasive breast cancer independent of adjuvant treatment and could also be valuable as prognostic factor for pre‐invasive DCIS. Highlights: Acid ceramidase (ASAH1) is a key enzyme of sphingolipid metabolism. ASAH1 is highly expressed in luminal A – like subtype of breast cancer. ASAH1 expressing tumors show improved prognosis independent of adjuvant treatment. Also in DCIS high ASAH1 is associated with a luminal phenotype. ASAH1 may be a valuable prognostic marker in both DICS and early breast cancer.